Wave-Function Symmetry Control of Electron-Transfer Pathways within a Charge-Transfer Chromophore - Aramburu-Trošelj, Bruno M.; Ramírez-Wierzbicki, Ivana; Scarcasale, Franco; Oviedo, Paola S.; Baraldo, Luis M.; Cadranel, Alejandro (Journal of Physical Chemistry Letters, 2020)
Despite a diverse manifold of excited states available, it is generally accepted that the photoinduced reactivity of charge-transfer chromophores involves only the lowest-energy excited state. Shining a visible-light laser pulse on an aqueous solution of the chromophore-quencher [Ru(tpy)(bpy)(μNC)OsIII(CN)5]- assembly (tpy = 2,2';6,2''-terpyridine and bpy = 2,2'-bipyridine), we prepared a mixture of two charge-transfer excited states with different wave-function symmetry. We were able to follow, in real time, how these states undergo separate electron-transfer reaction pathways. As a consequence, their lifetimes differ in 3 orders of magnitude. Implicit are energy barriers high enough to prevent internal conversion within early excited-state populations, shaping isolated electron-transfer channels in the excited-state potential energy surface. This is relevant not only for supramolecular donor/acceptor chemistry with restricted donor/acceptor relative orientations. These energy barriers provide a means to avoid chemical potential dissipation upon light absorption in any molecular energy conversion scheme, and our observations invite to explore wave-function symmetry-based strategies to engineer these barriers.
CRIS-Team Scopus Importer:2020-10-23